Virtue ethics and nursing: on what grounds? - Newham, Roger A. (Nursing philosophy, 2015)
Within the nursing ethics literature, there has for some time now been a focus on the role and importance of character for nursing. An overarching rationale for this is the need to examine the sort of person one must be if one is to nurse well or be a good nurse. How one should be to live well or live a/the good life and to nurse well or be a good nurse seems to necessitate a focus on an agent's character as well as actions because character is (for the most part) expressed in action (e.g. see Laird). This paper will give an overview of the reasons for the role and importance of character in nursing practice and explain its relation to nursing's frequent use of virtue ethics in order to recommend caution. While the paper agrees that the role of character is important in nursing caution is needed in both how much moral and thus normative, emphasis is being placed on the psychology of character and on the drift to virtue ethics. The psychological which may be explanatory needs to be linked with the normative, and a justification for the normative is needed. A justification as virtue ethics is contested, and nursing practice does not need to take on this explanatory and justificatory burden. A tentative proposal raised but not discussed in depth in this paper is that when an ultimate explanation or explanatory ground is needed, nursing practice leads quite naturally to a form of consequentialism as well as a realist metaethic. On this account, there are two levels of moral thinking, and nursing practice entails the virtues at one level and leads quite naturally to moral thinking at another more critical level of the criterion of what makes something right and good independently of character.